Processos educativos na comunidade jongueira de Anchieta: práticas de enfrentamento ao racismo na educação de jovens e adultos - Xavier, Francisco de Assis (2019)
The dissertation now socialized is the result of research carried out under the Graduate Program of Professional Master in Education (PPGMPE) of the Federal University of Espírito Santo (UFES) and aims to unveil the constitutive elements of Intangible Cultural Heritage in the jongueira community of Anchieta/ES Higher Education and the possible connections with pedagogical practices in the school system of that municipality. For such, the study privileged the analysis of the racial processes in the community education and the narratives of the involved ones in the research as basic premises to the understanding of the way in which the jongueiro identity construction is accomplished through the knowledge coming from its ancestors, as well as the perception of teachers and students to ethnic-racial relations in the school space. From field research in two school units and interviews with professionals and students of these establishments, as well as members of the Jongo de São Benedito Sol e Lua Group, it was possible to verify the intertwining of the boundaries established between the jongueiro territory and the school community, portrayed from the theoretical perspective of authors such as Santos (2005), Freire (2005; 2010), Bauman (2003), Munanga (2005), among others. From this research it was inferred that the cultural practices lived in the communities must go beyond the limits of the gates of the teaching units, so that the students can recognize themselves in the activities of the curriculum that are experienced there and this empathy generated during these experiences. an education intended to be liberating